Strong-adsorbability product capable of removing peculiar smell and releasing negative ions and preparation method thereof

By combining the inner and outer materials of a specific formula, combined with the drying and calcining process, the strong adsorption removal and negative ion products are solved, and the existing odor removal products are achieved, achieving efficient and long-term odor removal and air purification functions.

CN119857463APending Publication Date: 2025-04-22SHENZHEN PUHUA ECOLOGICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510064664.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The performance of existing odor removal products has decreased after use for a period of time, and is not strong in sustainability, and has safety hazards for easily sensitive people, or have weak adsorption and decomposition capabilities, so it is impossible to achieve odor removal effect in a short period of time.

Method used

The combination formula of the inner material and the outer material is adopted. The components of the inner material include bentonite, natural adsorption powder, diatomaceous earth and seporous powder. The components of the outer material include bentonite, natural adsorption powder, diatomaceous earth, seporous powder, negative ion powder and nanomaterials. Strong adsorption and odor release negative ion products are prepared through drying and calcining processes.

Benefits of technology

The products have excellent odor removal performance, good adsorption performance, anti-mildew and antibacterial properties, and insecticide and anti-itching functions. They have self-cleaning properties, can decompose formaldehyde benzene and benzene, and release negative ions to purify the air, meeting the long-term needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857463A_ABST
    Figure CN119857463A_ABST
Patent Text Reader

Abstract

The invention discloses a strong-adsorbability product capable of removing peculiar smell and releasing anions and a preparation method thereof.The product comprises an inner material and an outer material, the inner material comprises, by weight, 2%-5% of bentonite, 50%-60% of natural adsorption powder, 30%-42% of kieselguhr and 5%-10% of sepiolite powder; the outer material comprises the following components in percentage by weight: 2%-5% of bentonite, 72%-83% of natural adsorption powder, 8%-10% of diatomite, 5%-10% of sepiolite powder, 0.5%-3% of negative ion powder and 1%-2% of a nano material. Ecological balls or craft products with excellent peculiar smell removing performance, good adsorption performance, mildew-proof and antibacterial performance and insecticidal and itching relieving functions are manufactured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of negative ion products, and in particular to a product for removing odor and releasing negative ions with strong adsorption and a preparation method thereof. Background Art

[0002] People will produce a certain degree of odor in all aspects of their daily lives, such as the odor caused by kitchen waste, the odor caused by food residues in the corners, the odor of the bathroom sewer, the odor of shoes and shoe cabinets, the odor of quilt covers and pillow cases after long-term use, and the odor in the car, etc. Therefore, people need to use odor removal products frequently.

[0003] Existing odor removal products include: activated carbon type, flavor and fragrance type, and plant adsorption type. Activated carbon type products rely on the capillary adsorption capacity of activated carbon to achieve odor removal, but its adsorption capacity will gradually weaken and it is also easily affected by dust. After a period of use, its performance will drop significantly, and the sustainability of odor removal is not strong. The advantages are low cost and wide application. Flavor and fragrance type products remove odor by covering the odor with their own fragrance. They do not absorb or decompose the odor. Most of them just "cheat" the nose. There are safety hazards for sensitive people and may cause respiratory diseases. The advantages are fast onset and easy storage after opening. Plant absorption type refers to users planting special types of plants to absorb odors to achieve odor removal. The advantages are environmental protection, energy saving and strong sustainability. The disadvantages are weak adsorption and decomposition capabilities, and the odor removal effect cannot be achieved in a short time. There are also requirements for planting space and daily maintenance.

[0004] Therefore, there is an urgent need for a strong adsorption deodorizing and negative ion releasing product and a preparation method thereof that can solve one or more of the above problems. Summary of the invention

[0005] In order to solve one or more problems existing in the prior art, the present invention provides a strong adsorption deodorizing and negative ion releasing product. The technical solution adopted by the present invention to solve the above problems is: the product comprises: inner material and outer material, the weight percentage of each component of the inner material is: bentonite 2%-5%, natural adsorption powder 50%-60%, diatomite 30%-42%, sepiolite powder 5%-10%; the weight percentage of each component of the outer material is: bentonite 2%-5%, natural adsorption powder 72%-83%, diatomite 8%-10%, sepiolite powder 5%-10%, negative ion powder 0.5%-3%, nano material 1%-2%.

[0006] In some embodiments, the weight percentages of the components of the product are: 75% of the inner material and 25% of the outer material.

[0007] Furthermore, the inner material and the outer material are mixed and formed by a mold, or the inner material is made into a spherical shape, and the outer material wraps the inner material and is formed into a spherical shape.

[0008] In some embodiments, the natural adsorbent powder is a crystalline hydrated magnesium aluminum silicate mineral.

[0009] In some embodiments, the nanomaterial includes a first nanomaterial and a second nanomaterial, the weight percentage of the first nanomaterial is 0.5%-1%, and the weight percentage of the second nanomaterial is 0.5%-1%. For example, the first nanomaterial is nano titanium dioxide.

[0010] And a method for preparing the above product, which comprises: drying the product after forming, calcining it for 2 hours after drying, cooling it to room temperature after calcining, and the calcining temperature is 600 degrees. The drying time is 2-3 hours.

[0011] The technical effect achieved by the present invention is that the product manufactured by the above formula has excellent deodorizing performance, and also has good adsorption performance, mildew and antibacterial performance and insecticidal and antipruritic functions. It has self-cleaning properties and can decompose formaldehyde, benzene and benzene derivatives, and release negative ions to purify the air; furthermore, the manufacturing materials of the product meet the environmental protection requirements and have long-term deodorizing performance; after being used for a period of time, the product can be restored to performance by washing and drying to meet the long-term requirements.

[0012] The products are also very convenient to use. For spherical products, the diameter can be 8mm, with moderate hardness and not easy to break. They are resistant to water immersion and can be placed relatively casually where needed, such as pillowcases, cabinets, shoes, clothes, toilets, kitchens and cars, etc. On the premise of meeting performance requirements, the products can be made into handicrafts through mold molding to meet the user's aesthetic needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a schematic diagram of a spherical product of the present invention.

[0014] [Reference Signs]

[0015] 1. Inner material 2. Outer material. DETAILED DESCRIPTION

[0016] In order to make the above-mentioned objects, features and advantages of the present invention more understandable, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from this description, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0017] The invention discloses a strong adsorption deodorizing and negative ion releasing product, the product comprises: an inner material and an outer material, the weight percentage of each component of the inner material is: 2%-5% bentonite, 50%-60% natural adsorption powder, 30%-42% diatomite, 5%-10% sepiolite powder; the weight percentage of each component of the outer material is: 2%-5% bentonite, 72%-83% natural adsorption powder, 8%-10% diatomite, 5%-10% sepiolite powder, 0.5%-3% negative ion powder, 1%-2% nano material; wherein the weight percentage of each component of the product is: 75% of the inner material and 25% of the outer material. It should be pointed out that the natural adsorption powder can be attapulgite, i.e. palygorskite powder.

[0018] Specifically, the product can be made into various shapes according to the needs, such as: the inner material and the outer material are mixed and formed through a mold to finally make a handicraft or a part of a handicraft with aesthetics. Among them, the conventional shape of the product is spherical, such as Figure 1 As shown, the inner material 1 is made into a spherical shape, and the outer material 2 wraps the inner material 1 and is made into a spherical shape. The spherical product can be packaged with breathable cloth or non-woven fabric, or with a box with air holes, so as to be placed in respective usage scenarios.

[0019] Furthermore, for the components of the product, the nanomaterial includes a first nanomaterial and a second nanomaterial; in the weight percentage of the components of the external material, the weight percentage of the first nanomaterial is 0.5%-1%, and the weight percentage of the second nanomaterial is 0.5%-1%. Wherein, the first nanomaterial and the second nanomaterial are selected from materials with chemical stability, thermal stability, non-toxicity, super-hydrophilicity, and non-migratory properties, such as: photocatalytic nano-antibacterial materials (titanium dioxide and zinc oxide), silver antibacterial agents, etc., wherein the first nanomaterial is preferably titanium dioxide. For example: the first nanomaterial is nano titanium dioxide with a diameter of 30 nanometers, and the second nanomaterial is nano titanium dioxide with a diameter of 60 nanometers.

[0020] Experiments have shown that nano-titanium dioxide at a concentration of 0.1 mg / cm3 can completely kill malignant HeLa cells, and as the amount of superoxide dismutase (SOD) added increases, the efficiency of titanium dioxide photocatalysis in killing cancer cells also increases. The killing rate of nano-titanium dioxide on Bacillus subtilis black variant spores, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus, Salmonella, Trichoderma and Aspergillus is more than 98%; adding nano-titanium dioxide to the coating can produce antibacterial and antifouling coatings that are sterilizing, antifouling, deodorizing and self-cleaning. They are used in hospital wards, operating rooms and family bathrooms where bacteria are dense and easy to breed, and can purify the air, prevent infection, and deodorize.

[0021] Under the action of sunlight or ultraviolet light, titanium dioxide is activated and generates free radicals with high catalytic activity, which can produce strong photo-oxidation and reduction capabilities, and can catalyze and photo-decompose various organic substances such as formaldehyde, benzene and benzene series attached to the surface of objects and some inorganic substances, and can purify indoor air. Nano titanium dioxide has a strong "super hydrophilicity", and it is not easy to form water droplets on its surface. In addition, nano titanium dioxide can act on hydrocarbons under visible light. By using such an effect, a thin layer of nano titanium dioxide can be formed on the surface. The photocatalytic reaction of titanium oxide can decompose the organic pollutants adsorbed on the surface of titanium oxide into carbon dioxide and oxygen, which can be washed away by water together with the remaining inorganic substances, thereby realizing the self-cleaning function.

[0022] The main component of diatomite is silica, and there are countless pores on the surface, which can absorb and decompose the peculiar smell in the air, and has the functions of humidity control and deodorization. Adding titanium dioxide to diatomite to make a composite material can eliminate peculiar smell and absorb and decompose harmful chemicals for a long time, and can have long-term cleanliness. The natural adsorption powder is a crystalline hydrated magnesium aluminum silicate mineral, which is mainly used to provide strong adsorption performance (especially the absorption of ammonia smell), has a unique layer chain structure feature, has lattice substitution in its structure, contains an indefinite amount of Na+, Ca2+, Fe3+, Al3+ in the crystal, and the crystal is needle-shaped, fibrous or fibrous aggregate, and its water absorption is strong, and it has viscosity and plasticity when wet, but shrinks little after drying, does not show cracks, and collapses when soaked in water. Sepiolite is a hydrated magnesium-rich silicate clay mineral with a layered chain structure, orthorhombic or monoclinic crystal system, generally in the form of block, earthy or fibrous aggregates; Sepiolite has a slippery and astringent feeling, sticks to the tongue, is brittle in a dry state, has a low shrinkage rate, good plasticity, a large specific surface area, and strong adsorption, but is soluble in hydrochloric acid and is light in weight.

[0023] Each combination of the products is manufactured through reasonable proportions and preparation methods, thereby overcoming their own defects while maintaining the beneficial effects of each component.

[0024] The preparation method is as follows: the product is dried after molding, calcined for 2 hours after drying, and cooled to room temperature after calcination. The calcination temperature is 600 degrees, and the drying time is 2-3 hours.

[0025] During the calcination process of the product, the calcination temperature affects the hardness and deodorizing performance of the finished product, among which the hardness affects the water resistance and the stability of the fine pore structure of the finished product. That is, the calcination during the preparation process affects whether the finished product can be used for a long time, whether it is easy to clog pores, adsorption performance, and recoverability.

[0026] When the sepiolite powder is not added to the product: its strong adsorption performance mainly relies on the natural adsorption powder, the diatomaceous earth and the bentonite. In the calcination temperature range of 400 degrees Celsius to 1100 degrees Celsius, the lower the calcination temperature, the lower the hardness of the finished product, but the better the deodorization performance, and the higher the calcination temperature, the higher the hardness of the finished product, but the worse the deodorization performance. Among them, at 1000 degrees Celsius, the deodorization performance of the finished product is poor, the hardness is the highest, but other properties are slightly affected. When it is greater than 1000 degrees Celsius, the surface of the finished product will be ceramic vitrified, and then there will be no microporosity and all functional properties will be lost. In addition, too low a hardness will cause the finished product to be fragile and easy to powder.

[0027] When the sepiolite powder is added to the product, the adsorption performance of the finished product can be enhanced, and the sintering temperature of the calcination can be reduced, thereby reducing the calcination temperature of the hardness required for the finished product. According to the test, the calcination temperature is 600 degrees Celsius and the calcination time is 2 hours. The performance of the finished product is the best, which ensures the required hardness, excellent adsorption performance, and excellent deodorization performance.

[0028] The product manufactured by the preparation method has a negative ion concentration of 500-1000 per cubic centimeter after testing, which can purify the air, remove odors and kill bacteria, and is also beneficial to the health of users.

[0029] The product manufactured by the preparation method is tested by an ammonia test method, wherein the product (spherical) is placed in a 300 ml glass bottle, the product accounting for about two-thirds of the volume of the bottle, a small piece of folded paper towel is placed on the product, and then a drop of concentrated ammonia water is dripped on the surface of the paper towel, and then the lid is immediately tightened to seal the bottle. After timing for 5 minutes, the paper towel piece is taken out and quickly smelled with the nose, and then the bottle is smelled; the result is: there is almost no ammonia smell on the paper towel, and there is almost no ammonia smell in the bottle; the conclusion is: within 5 minutes, the product almost completely absorbs and decomposes the concentrated ammonia water, and has excellent odor removal performance.

[0030] Moisture absorption and humidity control function test: drop a drop of water on a glass plate, and then place the product in a spherical shape (8mm in diameter) on the water, and observe the time and amount of water absorption. The result is: the water is absorbed instantly; in humid weather (high humidity environment, humidity 80%), the moisture content of the product is detected to be about 25%; in dry weather (low humidity environment, humidity 30%), the moisture content of the product is detected to be about 8%; the conclusion is: the product has good moisture absorption and humidity control performance.

[0031] Anti-mildew, antibacterial and odor removal test: The product is divided into small grids and wrapped in an insole to make a test insole. Another ordinary insole is prepared, and a person with smelly shoes is asked to try it on. In the hot summer, according to the usual daily activities, the two insoles are put into the same type of shoes. Ordinary insoles: There is still foot odor after 10 hours, and the test insole: There is no obvious foot odor. The conclusion is: the deodorizing effect is obvious;

[0032] The two tested insoles were then sliced ​​and observed under a microscope to compare the number of bacterial species and the amount of bacteria on the two insoles. The results showed that the types and amounts of bacteria on the tested insoles were significantly less. The conclusion was that the deodorizing and antibacterial effects were obvious.

[0033] Test for removing odor of cigarettes: put the product (spherical) into a 300ml glass bottle, which occupies about two-thirds of the volume of the bottle, blow a puff of smoke into the bottle, immediately tighten the lid to seal the bottle, time it for 20 minutes, then open it and quickly smell it with your nose. The result is: no smell of smoke. The conclusion is: it is effective in removing odor of cigarettes.

[0034] In summary, the products manufactured by the above formula have excellent deodorizing performance, and also have good adsorption performance, mildew and antibacterial performance, insecticidal and antipruritic functions. They are self-cleaning and can decompose formaldehyde, benzene and benzene derivatives, as well as release negative ions to purify the air. Furthermore, the manufacturing materials of the products meet the environmental protection requirements and have long-term deodorizing performance. After being used for a period of time, the products can be restored to performance by washing and drying to meet the long-term requirements.

[0035] The products are also very convenient to use. For spherical products, the diameter can be 8mm, with moderate hardness and not easy to break. They are resistant to water immersion and can be placed relatively casually where needed, such as pillowcases, cabinets, shoes, clothes, toilets, kitchens and cars, etc. On the premise of meeting performance requirements, the products can be made into handicrafts through mold molding to meet the user's aesthetic needs.

[0036] The above-described embodiments only express one or more implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the patent of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.

Claims

1. A strong adsorption deodorizing and negative ion releasing product, characterized in that: The product comprises inner material and outer material, wherein the weight percentage of each component of the inner material is: 2%-5% bentonite, 50%-60% natural adsorption powder, 30%-42% diatomite, and 5%-10% sepiolite powder; the weight percentage of each component of the outer material is: 2%-5% bentonite, 72%-83% natural adsorption powder, 8%-10% diatomite, 5%-10% sepiolite powder, 0.5%-3% negative ion powder, and 1%-2% nano material.

2. The strong adsorption deodorizing and negative ion releasing product according to claim 1, characterized in that: The weight percentages of the components of the product are: 75% of the inner material and 25% of the outer material.

3. The strong adsorption deodorizing and negative ion releasing product according to claim 2, characterized in that: The inner material and the outer material are mixed and formed by a mold.

4. The strong adsorption deodorizing and negative ion releasing product according to claim 2, characterized in that: The inner material is made into a spherical shape, and the outer material wraps the inner material and is made into a spherical shape.

5. The strong adsorption deodorizing and negative ion releasing product according to claim 1, characterized in that: The natural adsorption powder is a crystalline hydrated magnesium aluminum silicate mineral.

6. The strong adsorption deodorizing and negative ion releasing product according to claim 1, characterized in that: The nano material comprises a first nano material and a second nano material, wherein the weight percentage of the first nano material is 0.5%-1%, and the weight percentage of the second nano material is 0.5-1%.

7. The strong adsorption deodorizing and negative ion releasing product according to claim 6, characterized in that: The first nano material is nano titanium dioxide with a diameter of 30 nanometers, and the second nano material is nano titanium dioxide with a diameter of 60 nanometers.

8. A preparation method for preparing the strong adsorption deodorizing and negative ion releasing product as claimed in claim 3 or 4, characterized in that: The product is dried after forming, and then calcined for 2 hours after drying. After calcination, it is cooled to room temperature. The calcination temperature is 600 degrees.

9. The preparation method according to claim 8, characterized in that: The drying time is 2-3 hours.